STUDI PERBANDINGAN PERBEDAAN KONSEPTUAL ANTARA SISTEM BASIS DATA RELASIONAL DENGAN SISTEM PENYIMPANAN DATA BERTIPE NON-RELASIONAL (NO-SQL) : EKSPLORASI PADA SERVER DATA CASSANDRA - Nugroho, Adi; Winarko, Edi (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2013)
Relational database system (RDBMS-Relational Database Management System) is a database system that has a very strong mathematical foundation and has many advantages, so it is generally accepted by almost vendor. Basically, there is nothing 'wrong' with a relational database system. However, with the emergence of a variety of Web applications today that require the higher performance of query, relational data base system was showing the queries performance that do not fit the user’s needs and expectations, because relational database system, for generate specific queries, often have to join data from two or more tables that relate. This process require relational database server to perform a data search (lookup) in the tables must be joined. These data searches require computing resources (processor performance and memory usage) that relatively high, so the performance of a relational database server typically decreasesas more data should be joined. This problems trying to be addressed by several vendor. Google with its BigTable, Amazon with its Dynamo, Yahoowith its PNUTS, and Facebook with its Apache Cassandra for example, using the non-relationaldata storage (Data Store) approach. The purpose of this paper is to introduce Apache Cassandra that is one of the very large non-relational systems, then compare to relational database systems.